2015
DOI: 10.1007/s12011-015-0244-4
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Zinc Levels and Myocardial Infarction

Abstract: The purpose of this study is to clarify the association between Zn levels and myocardial infarction (MI) using a meta-analysis approach. We searched articles in the PubMed, OVID, and ScienceDirect published as of November 2014. Thirteen eligible articles with 2886 subjects from 41 case-control studies were identified. Overall, pooled analysis indicated that subjects with MI had lower Zn levels than healthy controls (standardized mean difference (SMD) = -1.848, 95 % confidence interval (CI) = [-2.365, -1.331]).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…A meta-analysis indicated a significant association between zinc deficiency and MI (Liu et al, 2015). The short-term inhalation of ultrafine zinc particles alleviated myocardial dysfunctions and slowed down conversion of MI to heart failure in MI rats, which agreed with previous studies that EF increased with Zn content (Oster et al, 1993) and Zn supplementation to a cardioplegic solution reversed the loss of systolic function (Powell et al, 1995).…”
Section: Dysfunctions and Remodelingsupporting
confidence: 85%
“…A meta-analysis indicated a significant association between zinc deficiency and MI (Liu et al, 2015). The short-term inhalation of ultrafine zinc particles alleviated myocardial dysfunctions and slowed down conversion of MI to heart failure in MI rats, which agreed with previous studies that EF increased with Zn content (Oster et al, 1993) and Zn supplementation to a cardioplegic solution reversed the loss of systolic function (Powell et al, 1995).…”
Section: Dysfunctions and Remodelingsupporting
confidence: 85%
“…Thus, it has been suggested that serum zinc is a reliable diagnostic indicator for acute MI, and the extent of the fall has prognostic implications. In a meta-analysis with 2886 subjects from 41 case-control studies, the authors revealed that the subjects with MI had lower zinc levels in serum and hair than healthy controls 68 . Moreover, a recent study using zinc quartiles also demonstrated a significant inverse correlation between serum zinc levels and serum creatine kinase (CK), CK-MB, and cardiac troponin T levels 69 .…”
Section: Zinc Status In Cvdsmentioning
confidence: 99%
“…Improper zinc homeostasis is associated with the development of cardiovascular diseases [29]. Liu et al [30] conducted a meta-analysis aimed at assessing the relationship between Zn concentration in the body and the occurrence of MI. e results of 13 publications proved that patients with acute MI had lower Zn concentration than the control group.…”
Section: Discussionmentioning
confidence: 99%